Cognitive, Affective and Psycomotoric Aspects Related Risky Sexual Behavior Among Adolescents at the University Level (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2022)
The current phenomenon shows that teenagers are into the sexually active period quickly. This condition causes adolescents to be more vulnerable to experiencing adolescent reproductive health triad such as premarital sex, STI/HIV infections and drug abuse. Higher education is an educational institution whose students are teenagers who do not rule out experiencing these problems. This study aims to determine the cognitive, affective and psychomotoric factors related to risky sexual behavior among adolescents at the college level using a cross sectional approach. The research analysis sample was 750 students from 4 study programs in one of the universities in South Sumatra which were taken by using cluster random sampling technique. Data analysis includes univariable and bivariable analysis (chi square test). The results showed that 12% of students had risky sexual behavior where 3.5% had vaginal, anal or oral sex. In addition, the results of the bivariate analysis showed that the variables that were significantly related to risky sexual behavior included cognitive factors (knowledge), affective factors (attitudes, perceptions of norms, parental roles and self-efficacy) and psychomotoric factors (negative peer group behavior). This study recommends the need for access to adolescent-friendly reproductive health services with the principle of peer educator as a means of improving soft skills for adolescents related to adolescent reproductive health.